Nanobioprobe for the determination of pork adulteration in burger formulations. - Md. Eaqub, Ali; Shuhaimi, Mustafa, Assoc. Prof Dr.; Uda, Hashim, Prof. Dr.; Yaakob, Che Man, Prof. Dr; Foo, Kai Loong (Hindawi Publishing Corporation, 2013)
Link to publisher's homepage at http://www.hindawi.com/